Faktor Kontekstual, Bran Switching, Dan Keputusan Pembelian Operator Seluler Di Kota Denpasar - I Made Oka Santika; I Nyoman Nurcaya (Forum Inovasi Bisnis dan Manajemen, 2018)
In this era there are many mobile operators who offer various services with excellence and uniqueness of its own. Young consumers are more likely to follow trends, so they make operator purchases by alternating. This phenomenon shows that contextual and behavioral factors alternating brands lead to consumer purchase decisions. The purpose of this study is to explain the influence of contextual factors and brand switching on purchasing decisions. This research was conducted on the user of mobile operator in Denpasar City which domiciled in Denpasar City. Sample size taken as many as 120 people with purposive samling method. Data were collected by distributing questionnaires using a 5-point Likert scale to measure 15 indicators. The analysis technique used is multiple linear regression. The result of research indicate that contextual factor variable have positive and significant effect to purchasing decision. Brand switching variables have a positive and significant effect on purchasing decisions. This research is expected to be a consideration for cellular service providers in meeting the needs and desires of consumers and is expected to be used as a subject of further study and add references related to variables studied.